Pengaruh Pemberian Kalium Yodida terhadap Bobot Kelenjar Tiroid, Pertambahan Bobot Badan dan Suhu Rektal Kambing Peranakan Etawah Lepas Sapih - Widjaya, Nilawati (Fakultas Peternakan Universitas Jambi, 2012)
The study was conducted to investigate the effect of kalium iodide (KI) administration to tyroid gland weight, and body weight gain, and rectal temperature of postweaning PE goat. Nine postweaning PE goat alloted into three treatments : P0 (control), P1 (0.1 ml KI), and P2 (0.2 ml KI), KI administered twice a week. Variables observed were tyroid gland weight, final body weight and rectal temperature. Data analized by ANOVA using GLM procedure of SPSS. The weight of tyroid gland of P0, P1, P2 were 2.0988 mg, 1,5650 mg, and 2.0088 mg respectively. The treatmentÂ affected (P<0.05) bodyweight gainÂ without change of rectal temperature (P>0.05). Inconclusion, 0.1 ml KI adminitration twice a week increased body weight gain, lighter tyroid gland weight without effect to rectal temperature.